Let $p$ be prime number ($p\gt2$) and $a,b\in\mathbb Z$ ,$a+b\neq0$ ,$\gcd(a,b)=1$ how to prove that $$\gcd\left(a+b,\frac{a^p+b^p}{a+b}\right)=1~~\text{or}~~ p$$

Thanks in advance .


$\begin{align}&{\bf Hint}\ \ \rm\displaystyle {\left(a\!-\!b,\frac{a^p\!-b^p}{a-b}\right)} = \overbrace{(a\!-\!b,\,a^{p-1}\!+\cdots+b^{p-1}) = (a\!-\!b,\color{#C00}{pb^{p-1}})}^{\large \bmod a-b:\ \ a\ \equiv\ b} = (a\!-\!b,p)\\[.2em] &\rm\ \ \ by\ \ \ (a,b) = 1\:\Rightarrow\: (a\!-\!b,b) = (a,b)=1,\,\ therefore\ \,\rm (a\!-\!b,b^n) = 1\ \ by\ Euclid's\ Lemma. \end{align}$

Remark $\ $ It's a special case $\rm\ f(x) = x^p,\,\ x = a\ \ (so\ \ \color{#0A0}{f'(b)} = \color{#C00}{pb^{p-1}})\:$ of

Theorem $\rm\displaystyle\quad \frac{f(x)-f(b)}{x-b} \equiv\ \color{#0A0}{f\:'(b)}\pmod {x\!-\!b}\quad$ for $\rm\ f(x)\in \mathbb Z[x]$

Proof $\ $ By Taylor, $\rm\,\ f(x)\ =\ f(b) +\: f\:'(b)\ (x\!-\!b) \,+\, (x\!-\!b)^2\: g(x)\ \ $ for some $\rm\ g(x) \in \mathbb Z[x]$

  • 2
    $\begingroup$ Note: this is meant as a (big) hint, along with some conceptual background for further motivation. If you have any trouble filling in the details then please feel welcome to ask questions in comments, and I will gladly elaborate. $\endgroup$ – Math Gems Mar 25 '13 at 20:05
  • $\begingroup$ See also this answer. $\endgroup$ – Bill Dubuque Apr 22 '15 at 15:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.